Prospective intervention opportunities regarding device ownership and the reduction of damage to handheld ruggedized devices with shift workers. Issue 2 (27th September 2018) - Burch, Reuben F.; Strawderman, Lesley; Cannon, Angela B.; Vander Linde, Rebecca
Abstract: Industrial equipment such as ruggedized handheld computers, scanners, and label printers used within asset tracking environments are expensive to purchase and costly to repair. For organizations that use this equipment, there is value in understanding when and why damage occurs and how much of those costs are potentially associated with the employees' own sense of psychological ownership and organizational pride. Given the connection between psychological ownership and pride, the purpose of this study was to analyze employee surveys to determine what methods, tools, or programs could reduce repair and replacement while developing a stronger sense of ownership for ruggedized devices used in material‐handling industries by shift workers. Unstructured interviews about device repair with management from a large industrial company were utilized to create a multiple‐choice, anonymous online survey ( n = 353). Of the six interventions proposed, assigning the same device to the same employee every shift appeared to have the most consistent and positive response. Destruction rates and costs should be posted for employee viewing and managers of workgroups with consistently high destruction rates should receive additional training. An incentive‐based program for employees responsible for the least amount of device damage as well as an individual‐assignment of devices to employees may be considered. Applications for this student include providing a tool with which organizations can use to gauge employee ownership of equipment as well as to identify interventions that may aid in mitigating expenses associated with industrially rugged equipment.